S-Step BiCGStab Algorithms for Geoscience Dynamic Simulations - Anciaux-Sedrakian Ani; Grigori Laura; Moufawad Sophie; Yousef Soleiman (Oil & Gas Science and Technology, 2016)
In basin and reservoir simulations, the most expensive and time consuming phase is solving systems of linear equations using Krylov subspace methods such as BiCGStab. For this reason, we explore the possibility of using communication avoiding Krylov subspace methods (s-step BiCGStab), that speedup of the convergence time on modern-day architectures, by restructuring the algorithms to reduce communication. We introduce some variants of s-step BiCGStab with better numerical stability for the targeted systems.